PENGARUH PROFITABILITAS, LEVERAGE DAN KEPEMILIKAN MANAJERIAL TERHADAP HARGA SAHAM PADA PERUSAHAN MANUFAKTUR DI BEI 2016-2020 - Eva A. Ambarita; Corinna Wongsosudono; Tarwiyah (Fakultas Ilmu Sosial Dan Humaniora, Universitas Ibbi, 2024)
This study aims to analyze the factors that affect stock prices . The variables tested in this study are profitability, leverage and managerial ownership as independent variables. The dependent variable used is stock price . The population used in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange during the period 2017 6-20 20 as many as 25 companies. The sample in this study were 11 companies selected based on purposive sampling method. The data analysis technique used is multiple linear regression analysis using the SPSS version 25 application.The results of this study indicate that partially profitability and managerial ownership have a significant positive effect on stock prices . Meanwhile, leverage has no effect on stock prices . Simultaneously profitability, leverage and managerial ownership have a significant effect on stock prices. .The conclusion of the research is that partially profitability and managerial ownership have a significant positive effect on stock prices , but leverage has no effect on stock prices . Simultaneously profitability, leverage and managerial ownership have a significant effect on stock prices.